Schreber’s gardens and Jordan’s gardens as elements of created nature: the example of Katowice - Nakonieczny, Ryszard (Polskie Studia Krajobrazowe, 2019)
The author analyzes historical examples of allotment gardens as well as sports and recreational grounds in Katowice (Poland) to underscore their importance for the appeal of the city and its ecology. Schreber’s and Jordan’s gardens of Katowice epitomize broader relationships between the human and nature observed in a typical contemporary city of the 20th century, where nature has crucial significance for the psychological and physical well-being, ensuring one an opportunity for leisure, promoting health, a sense of comfort, as well as activating all senses, which have become dulled today due to the impact of the virtual worlds. The author also outlines his own urban activities, which attempt to draw attention of city dwellers to the advantages of green areas.